2021
DOI: 10.1016/j.ijid.2021.08.062
|View full text |Cite
|
Sign up to set email alerts
|

High seroprevalence of SARS-CoV-2 but low infection fatality ratio eight months after introduction in Nairobi, Kenya

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
45
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 33 publications
11
45
1
1
Order By: Relevance
“…Our results are generally consistent with other community surveys conducted in Kenya at a roughly similar time point during the pandemic. In two household surveys conducted in Nairobi in November-December 2020, overall seroprevalence was 34.7% and 43.3%, 10,20 where we found a seroprevalence of 32.4% in Nairobi in January 2021; we observed similar age related seroprevalence patterns compared to the previous surveys.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our results are generally consistent with other community surveys conducted in Kenya at a roughly similar time point during the pandemic. In two household surveys conducted in Nairobi in November-December 2020, overall seroprevalence was 34.7% and 43.3%, 10,20 where we found a seroprevalence of 32.4% in Nairobi in January 2021; we observed similar age related seroprevalence patterns compared to the previous surveys.…”
Section: Discussionsupporting
confidence: 81%
“…The results are therefore more generalizable to the Kenyan population than previous studies that involved special populations. [2][3][4][5][6] Although there had been two other population-based studies 10,20 conducted earlier, both were limited to Nairobi, the capital city of Kenya. Our inclusion of other sites in this study, far removed from Nairobi, helps to provide broader insights into the extent of the SARS-CoV-2 pandemic in Kenya.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the early phase of the pandemic, epidemiologic data from the region suggested lower morbidity and mortality in the region, attributed to factors such as youthful population, favorable weather, and prior exposure to cross-reactive viruses [7]. However, later studies showed infections rates comparable to global trends, but significantly lower levels of severe disease and mortality [8].The emergence of VoCs with global impact in the later phase of the pandemic was associated with increased disease severity, rapid transmission, and re-infection of vaccinated or previously infected persons, continuing to strain the global public health infrastructure and economies despite availability of effective vaccines [9]. Among the VoCs that had global impact were B.…”
Section: Introductionmentioning
confidence: 99%
“…15,22,23 Access to hospital care is limited and varies within and across countries and regions. 24,25 The burden of SARS-CoV-2 infection, including severe disease requiring hospitalization, is underestimated in sub-Saharan Africa [26][27][28] and is potentially more underestimated among children, who are less likely to be evaluated for infection. 15 To address this issue, the present study assessed clinical manifestations, outcomes, and factors associated with outcomes among children and adolescents hospitalized with COVID-19 in 6 countries in sub-Saharan Africa.…”
mentioning
confidence: 99%